Port Trust War Memorial - Ghosh, Ayan (2023)
The Port Trust War Memorial was installed in 1919 as a traffic roundabout, located at the junction of three streets; SS Ramgulam Road, N Morarji Road, and Shoorji Vallabhdas Road. The pedestal is irregularly hexagonal, with commemorative plaques fixed on the three larger sides. The pedestal supports a circular, fluted column crowned with a metal lamp on top.